Sparse Matrix for ECG Identification with Two-Lead Features - Kuo-Kun Tseng; Jiao Luo; Robert Hegarty; Wenmin Wang; Dong Haiting (The Scientific World Journal)
Electrocardiograph (ECG) human identification has the potential to improve biometric security. However, improvements in ECG identification and feature extraction are required. Previous work has focused on single lead ECG signals. Our work proposes a new algorithm for human identification by mapping two-lead ECG signals onto a two-dimensional matrix then employing a sparse matrix method to process the matrix. And that is the first application of sparse matrix techniques for ECG identification. Moreover, the results of our experiments demonstrate the benefits of our approach over existing methods.